Implementation of the BPJS Health Referral Program in Indonesia: Literature Review - Jery Ardhan; Rizma Adlia Syakurah; Haerawati Idris; Yuanita Windusari (Indonesian Journal of Global Health Research, 2025)
BPJS Health's Reverse Referral Program (PRB) is an initiative designed to ensure continuity of care for patients with chronic diseases by coordinating between primary healthcare facilities (FKTP) and partner pharmacies. This article aims to review the available literature on the effectiveness of PRB drugs, the flow of referral services, drug availability, and the role of partner pharmacies in supporting program implementation. The method used was a Systematic Literature Review using the Preferred Reporting Items for Systematic Reviews (PRISMA) flow by collecting articles from the Science Direct, Pubmed and Google Scholar databases published between 2019 and 2024 with the keywords "BPJS Referral Program", "Referral Drug Effectiveness", "PRB Drug Availability", and "BPJS Partner Pharmacies". From the initial search results, 39 articles were found (3 articles from ScienceDirect, 11 articles from PubMed, and 25 articles from Google Scholar). Based on the analysis conducted, 6 articles were double-published, 5 articles were incomplete, and 8 articles were not relevant to the topic. Then, after selection, 20 articles were identified as meeting the inclusion criteria. The results of the analysis showed that PRB helps improve patient compliance in chronic disease management and reduces the burden on referral hospitals. However, challenges faced include limited drug distribution, logistical constraints, and suboptimal coordination. This review concludes that technology-based solutions and increased regulatory capacity are needed to ensure the overall effectiveness of this program.